Dekonstruksi Makna dalam Kumpulan Puisi Selamat Menunaikan Ibadah Puisi Karya Joko Pinurbo: Kajian Semiotika - Chairunnisa Br Pulungan; Diah Kusyani; Lailan Syafira Putri Lubis (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to deconstruct the meanings embedded in Joko Pinurbo’s poetry collection Selamat Menunaikan Ibadah Puisi through the perspectives of Roland Barthes’ semiotics and Jacques Derrida’s deconstruction theory. Employing a descriptive qualitative method with a semiotic textual analysis approach, the study analyzed 47 poems from the poetry collection Selamat Menunaikan Ibadah Puisi by Joko Pinurbo by examining their denotative and connotative meanings as well as the socio-cultural contexts represented in the texts. The findings reveal that connotative signs function as the primary mechanism for deconstructing established meanings, while ordinary domestic symbols are transformed into critical reflections on social, cultural, and spiritual issues. The poems challenge binary oppositions, particularly the sacred–profane dichotomy, generating multiple interpretations and rejecting fixed meanings. Furthermore, the analysis highlights critiques of moral crises, urban dehumanization, and social hypocrisy while reaffirming humanistic values, cultural syncretism, empathy, and inner sincerity. The study concludes that Joko Pinurbo’s poetry employs language as a subversive medium to question dominant ideologies and expand literary interpretation.